Doble nacionalidad y forum patriae en divorcios internacionales - Maestre Casas, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
The Court then analyses the question of whether, in order to determine the court which has jurisdiction in respect of the divorce of persons having the same dual nationality, only the nationality of the Member State with which those persons have the closest links is to be taken into account, or whether, on the contrary, both nationalities are to be taken into account, so that the courts of those two Member States can have jurisdiction on that basis, at the choice of the persons concerned. The Court establishes that the grounds set out in matrimonial matters are alternatives, without any hierarchy between them. A person possessing dual nationality can choose between the courts of two Member States which are competent exclusively on grounds of nationality. This necessarily entails a right of choice on the part of the applicant.
Keywords: Jurisdiction and the recognition and enforcement of judgments in matrimonial matters; transitional provisions of Regulation 2201/2003; dual nationality of two Member States